PENGARUH TINGGI MUKA AIR TANAH TERHADAP pH, Eh, Fe, Aldd, Mn DAN P TERLARUT PADA TANAMAN NANAS KLON GP3 DI ULTISOL - Ayu Sulistya Kusumaningtyas; Priyo Cahyono; S Sudarto; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2015)
Water logging is a condition where water can concentrate at one location. This condition can cause changes in soil chemical properties and inhibiting the growth of pineapple plant of PT. Great Giant Pineapple. The purposes of this study were to understand the influence of soil water level on the change in soil chemical properties in different soils iron content, and the influence of soil water level on plant growth as well as iron and phosphorus absorption in plants. This study used factorial completely randomized design with 30 treatment combinations. The treatments included soil with 100% water available, 0 cm from soil surface, 10 cm from soil surface, 20 cm from soil surface, 30 cm from soil surface, 12.76 ppm iron concentration and 30.15 ppm iron concentration. The The results showed that the water level was significantly different on pH, Fe, exchangeable Al, exchangeable H, and Eh in soil iron and not significantly different on Mn, P and pineapple plant growth in 6 weeks of waterlogged. The soil water content did not significantly change soil pH . Therefore, the response to pineapple plant growth was not significantly different. The best treatment for water logging was 30 cm of water logging from surface